The Factors Affecting Employee Work Productivity in the Bengkulu Province Community and Village Empowerment Service (Dpmd) - Desmonda Tertia; Sri Handayani; Yanto Effendi (Universitas Dehasen Bengkulu, 2023)
Work productivity refers to the general attitude of an individual towards work. A person with a high level of work productivity shows a positive attitude towards his work, and on the contrary if the employee is dissatisfied with his job, the employee will show a negative attitude towards his work. This study aims to determine the factors that can affect the work productivity of employees at the Community and Village Empowerment Service of Bengkulu Province. The sample in this study were 43 employees at at the Community and Village Empowerment Service of Bengkulu Province. The sampling technique is a census by using questionnaire data collection and the analytical method used is validity test, reliability test, coefficient of determination, multiple linear regression and hypothesis testing. The results of this study are: a). Based on the three factors that affect work productivity, there is no significant correlation between leadership, compensation and work environment on employee work productivity at at the Community and Village Empowerment Service of Bengkulu Province. It can be seen that the significance value of leadership is 1.120 which is smaller than 1.683 where t count < t table, as well as the significance value for compensation of 0.049 which is smaller than 1.683 because t count < t table, and also the work environment significance value obtained is 0.646 smaller than 1.683 where t count <t table. b). The ability of leadership, compensation and work environment in the Community and Village Empowerment Service of Bengkulu Province in influencing the work productivity of its employees is only 4.3%, while the remaining 95.7% is affected by other causal factors which were not examined in this study.